The prevalence of Stafne bone cavity: A meta-analysis of 355,890 individuals - Phanthip Chaweeborisuit; Laphatrada Yurasakpong; Nutmethee Kruepunga; R. Shane Tubbs; Arada Chaiyamoon; Athikhun Suwannakhan (Elsevier, 2023)
Background/purpose: A Stafne bone cavity (SBC) is an incidental depression in the lingual surface of the mandible. The aim of this study is to provide pooled estimates of the frequency of Stafne bone cavity and to correlate its presence with such variables as sex, laterality, diagnostic methods and population. Materials and methods: Potential studies were searched through four electronic databases: Google Scholar, PubMed, Scopus, and Journal Storage. Titles, abstracts, and full texts of the articles were screened. Results: A total of 54 studies relating to 355,890 subjects met the inclusion criteria for meta-analysis. A meta-analysis using the DerSimonian-Laird model revealed an overall prevalence of 0.17% (CI:0.14%-0.21%, I2 = 80.7%). SBC was four times more common in males than females (z = 6.94, P < 0.01), and was unilateral in almost all cases (z = 12.90, P < 0.01). Radiographic studies yielded a lower SBC prevalence at 0.12% (CI:0.09%-0.15%, I2 = 71.7%) than computed tomography studies, skeletal studies and excavation studies. Ancient populations had three times higher SBC prevalences (0.47%, CI:0.21%-0.73%, I2 = 89.5%) than the average populations today (z = 3.21, P < 0.01). Conclusion: The prevalence of Stafne bone cavity is approximately 0.17%, and was four times more prevalent in males than females. This variant bone cavity was also present unilaterally in the majority of cases. Awareness of SBC is important for dentists, maxillofacial surgeons and other practitioners performing routine dental practices and interpreting panoramic radiographs.